Co-production of hydrogen and power from palm mill wastes. (February 2019) - Darmawan, Arif; Ajiwibowo, Muhammad W.; Cahyo, F. Anggoro; Aziz, Muhammad; Tokimatsu, Koji
Abstract: An integrated system to harvest efficiently the energy from palm mill wastes, which are empty fruit bunch (EFB) and palm oil mill effluent (POME), is proposed and evaluated. The proposed system adopts the supercritical water gasification (SCWG) of mixed EFB and POME, which is integrated with also with chemical looping and power generation. To minimize the exergy loss throughout the system, and therefore, optimize the energy efficiency, process design and integration is conducted by employing the principles of exergy recovery and process integration technologies. Hydrogen is set as the main output, while power is produced by utilizing the heat generated throughout the process. Process simulation is conducted using a steady state process simulator Aspen Plus V8.8. Energy efficiency is defined into three categories: hydrogen production efficiency, power generation efficiency, and total energy efficiency. From process simulation, the integrated systems show high total energy efficiency. Further study should be performed to investigate the effect of EFB/POME ratio, gasification temperature, SCL pressure condition on the system performance including total energy efficiency.